Compression molded composites from discarded nylon 6/nylon 6, 6 carpets for sustainable industries. (20th March 2016) - Pan, Gangwei; Zhao, Yi; Xu, Helan; Hou, Xiuliang; Yang, Yiqi
Abstract: Discarded carpets with high amount of petroleum-based fibers are usually disposed in landfills, leading to waste of high value petro-polymers and environmental pollution. A novel method to reuse nylon carpet targeting environmental protection and material saving was developed. Recent studies showed that melt blended nylon carpet composites by screw extruder had low mechanical properties and disqualified carpet composites in transportation and construction industries. In this research, compression molded composites from discarded nylon 6/nylon 6, 6 carpets had good sound absorption, mechanical properties and water stability. As compared with jute/PP composites, the compression molded composites from nylon 6/nylon 6, 6 carpets had up to 40%, 59%, 124% and 32%, higher sound absorption, flexural strength, elastic modulus and impact resistance, respectively. Unshredded nylon 6, 6 carpet yarns and styrene-butadiene-rubber/calcium-carbonate binders in carpets reinforced nylon 6 and polypropylene, and thus made the composites strong. Styrene-butadiene-rubber particles and multiple interfaces in the multi-component composites endowed compression molded nylon 6/nylon 6, 6 carpet composites with good sound absorption. Developing compression molded carpet composites with good mechanical properties and sound absorption provides a new method of reusing carpets. Highlights: Nylon carpets have been reused for environmental protection and material saving. Composites from nylon carpets have good sound absorption and tensile properties. Good sound absorption is due to SBR and multiple interfaces in the composites.